Perkembangan dan implementasi keadaan memaksa di Indonesia - Putri, Febi Ananda (Maliki Interdisciplinary Journal, 2024)
This research aims to find out more about the development and implementation of force majeure in Indonesia. In answering this objective, this study used the library research method, which is research carried out by utilizing literary sources such as books, notes, scientific journals and previous research reports. By using library research methods, it can be concluded that the development of force majeure in Indonesia when compared with the scope of force majeure regulated in the Civil Code, there has been significant development. Today, the scope of force majeure is not only limited to natural events or external forces, as well as the loss of promised objects, but has also expanded to include administrative acts of authorities and political conditions such as war. Subsequent developments show that it turns out that the coercive situation that makes it impossible for the debtor to fulfill his promise is not always absolute, but the coercive situation in question can be relative, meaning that the debtor still has the choice to carry out or not carry out his obligations, but it requires a lot of sacrifice if the debtor carries out his obligations. Meanwhile, the implementation of force majeure in contracts, the implementation of force majeure in Indonesia occurs in various situations, such as in business contracts, employment relationships, and procurement of goods and services by the government. If the application of force majeure is carried out haphazardly, when in reality the company is still able to fulfill its obligations, what will happen is only a shift in risk responsibility.